DOUBLE DIFFUSION STUDIES IN THE SOUTHERN INDIAN OCEAN (ALONG 95OE FROM 45OS TO 10OS) - Syofian, Joni
Double diffusion is divided into two, namely salt finger and convection diffusion which can occur due to the accumulation of several water masses (interleaving). To determine the incidence of double diffusion along 95oE from 45oS to 10oS, CTD data from observations from the R/V Roger Revelle ship was used from March 4, 2016-April 3, 2016. The determination of the type and percentage of double diffusion that occurs is based on Turner angle values obtained using The Gibbs-SeaWater (GSW) Oceanographic Toolbox TEOS-10. It was found that there was a pile of water masses between South Indian Central Water (SICW), Indonesian Upper Water (IUW), and Indian Equatorial Water (IEW) above Australasian Mediterranean Water (AAMW), Antarctic Intermediate Water (AAIW) and Indian Deep Water (IDW) which caused double diffusion. The salt finger phenomenon is more dominant than convection diffusion with successive percentages of 41.01% and 0.76%, respectively. The percentage of salt finger active in the area was 9.30% while the active diffusion of convection was 0.17%. Based on potential density anomalies (????????), the incidence of double diffusion of salt finger is most prevalent in ???????? 26.9 kg/m3 is 100% however, the percentage of active salt finger is most prevalent in the ???????? 26.8 kg/m3 is 83.85%. Meanwhile, the incidence of convection diffusion is found in the ???????? 26.7 kg/m3 is 6.3% and the most active diffusion of convection was also found in the ???????? 26.7 kg/m3 which is 5.51%.